A B C D is a trapezium such that A B is parallel to C D , A B = 1 1 , C B = 4 , C D = 6 and A D = 3 . Find the height of the trapezium (perpendicular distance of C D and A B ).
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Through D , draw a line parallel to B C . Let it meet A B in E . Then, quadrilateral B C D E is a parallelogram because its opposite sides are parallel. Therefore, D E = 4 . And, A E = A B − B E = 1 1 − D C = 5 .
Thus, Δ A D E is a 3-4-5 right triangle. Thus, if h is the height(length of perpendicular from A) of the triangle then, a r ( Δ A D E ) = 2 1 3 × 4 = 2 1 5 × h h = 2 . 4
My approach is Algebraic.
For this one important formula is to be applied, which is that area of a quadrilateral is ( s − a ) ( s − b ) ( s − c ) ( s − d ) where s is the semi perimeter of the quadrilateral and a , b , c , d are the sides. And for obtaining the height we have to equate this with the normal formula for calculating the area of a Trapezium which is 2 1 ( s u m o f p a r a l l e l s i d e s ) ∗ h e i g h t .
We get s = 2 4 and the sum of the parallel sides as A B + C D = 1 7 .
so 1 2 3 = 2 1 ∗ 1 7 ∗ h e i g h t . and the height comes out to be
= 1 7 2 4 3 ≈ 2 . 4 4
But it comes 2 . 4 directly without any approximation
i got 2.4452 from the calculator and as it is an irrational number i approximated it.
Log in to reply
But see @Chew-Seong Cheong 's Solution. No 3 is there. Ok, then also leave it
This is wrong. The area of a quadrilateral is ( s − a ) ( s − b ) ( s − c ) ( s − d ) if and only if it is CYCLIC.
Problem Loading...
Note Loading...
Set Loading...
Let the height of the trapezium be h . By Pythagorean theorem, we have:
A D 2 − h 2 + C B 2 − h 2 3 2 − h 2 + 4 2 − h 2 9 − h 2 + 1 6 − h 2 9 − h 2 + 2 ( 9 − h 2 ) ( 1 6 − h 2 ) + 1 6 − h 2 2 ( 9 − h 2 ) ( 1 6 − h 2 ) ( 9 × 1 6 − 2 5 h 2 + h 4 9 × 1 6 − 2 5 h 2 + h 4 h 2 ⟹ h = A B − C D = 1 1 − 6 = 5 = 2 5 = 2 h 2 = h 2 = h 4 = 2 5 9 × 1 6 = 5 3 × 4 = 2 . 4 Squaring both sides. Squaring both sides.